Perlindungan Hukum Nasabah sebagai Konsumen Perbankan terhadap Kejahatan Skimming - Hadi, Ditmar; Widiarty, Wiwik Sri; Tobing, Gindo L. (Syntax Corporation, 2023)
Based on this background, there are several main problems in this writing, namely how legal protection for bank customers in the event of skimming crimes and how dispute resolution efforts can be made by bank customers in the event of skimming crimes. The legal theories used are the theory of legal protection from John Austin and the theory of justice from John Rawls. The research method is juridical normative and the data collection tools used are document or literature studies and interviews. The results of the existing research are Legal protection for bank customers in the event of skimming crimes consists of two types, namely indirect legal protection and direct legal protection. Next about dispute resolution. Dispute resolution that can be done by bank customers in the event of skimming crimes can be taken through non-litigation channels and through litigation channels. Dispute resolution through non-litigation channels, where banks are responsible for the refund of customer funds lost due to skimming by mediating for simple, cheap and fast dispute resolution. Meanwhile, if the customer is not satisfied with the compensation due to skimming, the customer can resolve the dispute through the court.